Phenomenological interviews with graduates from Psychiatric Institution: stories of experiences - Taiane Soares Vieira; Claudete Ferreira de Souza Monteiro (Universidad de Alicante, 2012)
This article aims to describe my experience in applying the method of Heideggerian research, in particular the phenomenological interviews with people with mental illness discharged from psychiatric institutions that are currently residents of Therapeutic Residential Services (SRTS). We interviewed nine residents of SRTs in Piauí. In this step several times to walk were striking as the strategy of rapprochement with the interviewees, the location of interviews and even stirring account of the subjects. This experience enabled me to identify what is necessary and important to establish empathy with the subjects, there is no formula for conducting the interview, but it is the researcher to identify the best strategy for obtaining the reports. So is that the empathetic experienced by me in getting the reports of respondents in essence residents through phenomenological interview was crucial to uncovering the meaning of the subjects lived in the daily life of these devices.